2020
DOI: 10.3390/w12051329
|View full text |Cite
|
Sign up to set email alerts
|

Farmer Cooperation in Participatory Irrigation in South Asia: Insights from Game Theory

Abstract: Participatory irrigation, where farmers are given greater control and management responsibility, has been a topic of controversy for many years. Initially seen as a panacea for dealing with weaknesses in state-run irrigation, participatory irrigation has generated mixed results, especially in South Asia. Part of the challenge of understanding the conditions that promote and undermine participatory irrigation is that it is seldom deployed in the same way. For example, irrigation fees collected by farmers are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Others have posited that retaining revenues locally in participatory irrigation management can engender greater compliance by farmers but simultaneously found that compliance itself requires the support of the state/provincial government (see, [22]). Similar complicated interactions are evident in this preference data.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have posited that retaining revenues locally in participatory irrigation management can engender greater compliance by farmers but simultaneously found that compliance itself requires the support of the state/provincial government (see, [22]). Similar complicated interactions are evident in this preference data.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…With this in mind, this study drew upon evidence in two states in east India-Assam and Bihar-and two provinces in Pakistan-Punjab and Sindh. The hydrological and agricultural setting for these case sites is reported in Hone et al [22].…”
Section: The Challenges Of Participatory Irrigation In India and Pakistanmentioning
confidence: 99%
“…The key finding from this ambitious work was that there is considerable diversity of preferences across and within jurisdictions. As with Hone et al [13], Burton, Cooper, and Crase [14] conclude that there is no simple universal panacea to enhancing the performance of PIM and understanding the local setting is paramount.…”
Section: Empirical Analysis Of Pim Using Behavioural Economicsmentioning
confidence: 94%
“…Diverting from the empirical modelling of institutional survey data, Hone et al [13] harness the rationale embodied in game theory to specifically consider what would motivate farmers to be more compliant with rules established under PIM. By contemplating the farmer's decision as a potential payoff matrix, they identify both cooperative and uncooperative equilibria.…”
Section: Empirical Analysis Of Pim Using Behavioural Economicsmentioning
confidence: 99%
“…However, we also find that it is unlikely to be a singular fix. We use empirical evidence to demonstrate the conundrums of making participatory irrigation sustainable [26]. Irrigation water can increase rice production, productivity, and farmers' revenue through the restoration of irrigation infrastructure, utilization of biological fertilizers, and proper management of irrigation systems.…”
Section: The Restoration Of the Tertiary Irrigation Network In Kendal...mentioning
confidence: 99%